2021
DOI: 10.2147/jir.s301663
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Key Genes of Sepsis and Septic Shock Using Bioinformatics Analysis

Abstract: Sepsis is a disease associated with high mortality. We performed bioinformatic analysis to identify key biomarkers associated with sepsis and septic shock. Methods: The top 20% of genes showing the greatest variance between sepsis and controls in the GSE13904 dataset (children) were screened by co-expression network analysis. The differentially expressed genes (DEGs) were identified through analyzing differential gene expression between sepsis patients and control in the GSE13904 (children) and GSE154918 (adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 67 publications
(74 reference statements)
3
19
0
Order By: Relevance
“…Progressively dysregulated in controls, septic patients and patients with septic shock, CD247 expression was modified by methylation. 108 CD247 expression positively correlated with patient survival at 28 days, 109 and CD247 may also be used to differentiate between patients with sepsis and systemic inflammatory response syndrome. 110 This result indicates that it plays an important role in sepsis, but the specific role and mechanism require further investigation.…”
Section: Diseasesmentioning
confidence: 97%
“…Progressively dysregulated in controls, septic patients and patients with septic shock, CD247 expression was modified by methylation. 108 CD247 expression positively correlated with patient survival at 28 days, 109 and CD247 may also be used to differentiate between patients with sepsis and systemic inflammatory response syndrome. 110 This result indicates that it plays an important role in sepsis, but the specific role and mechanism require further investigation.…”
Section: Diseasesmentioning
confidence: 97%
“…For example, PRKACB in M13 was recently reported as a potential biomarker in sepsis. 14 PRKACB, encoding the catalytic subunits of PKA, was down-regulated in chronic traumatic encephalopathy. 15 SMAD3 in M13 is prognostic for survival ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 99%
“…The low expression of CD247 can cause damage to the immune system and affect lymphocyte proliferation and cytokine production. The expression of CD247 is gradually downregulated during the development from sepsis to septic shock [ 20 ]. Jiang et al found that CD247 was the hub gene of sepsis through bioinformatics analysis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…e expression of CD247 is gradually downregulated during the development from sepsis to septic shock [20]. Jiang et al found that CD247 was the hub gene of sepsis through bioinformatics analysis [21].…”
Section: Discussionmentioning
confidence: 99%